We and They in Romans - Malina, Bruce J. (HTS teologiese studies, 2002)
According to cultural anthropologists ingroup/outgroup divisions are fundamental to Mediterranean views of the world. This essay considers Paul’s in-group/outgroup, or “we/they” perceptions. The ethnocentrism revealed in this dichotomy indicates that Paul, like other Mediterraneans of his time, showed little interest in the outgroup. Not surprisingly, neither was the God of Israel. Non-Israelites simply did not fit into the divine plan of things until non-Israelites, some centuries later, began to identify with Paul’s “we” – something Paul did not foresee.